A comprehensive and comparative evaluation of primers for metabarcoding eDNA from fish. Issue 12 (26th September 2020) - Zhang, Shan; Zhao, Jindong; Yao, Meng
Abstract: Accurate assessments of fish species diversity and community composition are essential for understanding fish ecology and conservation management. Environmental DNA (eDNA) metabarcoding has become an integrated method for monitoring fish species. The accuracy and efficacy of eDNA metabarcoding rely heavily on the choice of primers used for PCR amplification. A wide selection of metabarcoding primers for fish has been developed; however, there exists no comprehensive and comparative evaluation of their amplification or taxonomic classification of a rich diversity of fish species, which hinders informed decisions regarding their suitability for different study systems. Here we reviewed the literature and compiled a list of 22 primer sets for eDNA‐based metabarcoding analysis of teleost fish, the performance of which was compared using in silico PCR, followed by in vitro metabarcoding analysis using eDNA from waterbodies in Beijing, which harbour a high number of freshwater fish species. We found that the primers showed considerable differences in the amplified taxonomic ranges and proportions, fish taxa richness, species discrimination power and fish community compositions, both in silico and in vitro. The number of fish taxa detected from eDNA by the primer sets varied from 0 to 66. Primers targeting the 12S rRNA gene generally detected greater fish diversity than those targeting the 16S rRNA or COI genes, while primers targeting the cytochrome b gene amplified the fewest fish taxa in vitro. Regarding target genes, 12S primers generally outperformed other primers in terms of amplified fish diversity. The results of in silico PCR and in vitro tests were not always in agreement, suggesting that primer choice for biodiversity surveys should not be based solely on in silico evaluation. The use of different primers can qualitatively and quantitatively affect the detected biodiversity and these effects should be considered in experimental design and data interpretation. These results will assist with primer selection for eDNA‐based fish surveys, and consequently support conservation of freshwater biodiversity. 摘要: 准确评估鱼类物种多样性及群落构成对于了解鱼类生态及保护管理至关重要。环境DNA (environmental DNA, eDNA)结合宏条形码技术是一种鱼类检测的新兴方法。在影响eDNA方法检测准确性和有效性的诸多因素中, PCR引物和条形码区段的选择极为关键。随着eDNA方法的发展, 不同研究者设计出多种鱼类宏条形码通用引物, 由于缺乏标准化的实验流程和具有丰富物种多样性的eDNA样品对这些引物进行全面评估, 难以比较不同引物的扩增表现和相应宏条形码对鱼类多样性的检测能力, 不利于针对不同生态系统选择最适引物进行鱼类研究。 本研究首先通过文献检索筛选得到22对应用于硬骨鱼类eDNA宏条形码研究的引物, 继而利用基于计算机模拟的in silico PCR和基于北京水体提取的eDNA进行in vitro宏条形码分析对这些引物的性能进行全面比较。 In silico和in vitro的研究结果均显示这些引物在对不同生物类群的扩增范围和比例、检测鱼类物种丰富度、物种分辨度和鱼类群落构成等方面存在明显差异。在eDNA宏条形码分析中, 22对引物检测出的鱼类分类单元数范围为0～66。大部分线粒体DNA 12S基因区段的引物相比于16S和COI区段的引物检测出更高鱼类多样性, 而Cytb区段的引物扩增出的鱼类分类单元数最少。 综上, 从引物的目标基因来看, 12S区段的引物对鱼类多样性的扩增表现通常优于其他区段的引物。In silico与in vitro的引物评估结果存在差异, 因此不应仅依据in silico结果进行引物选择。不同引物的使用会对检测到的生物多样性产生定性和定量的影响, 这些影响在实验设计和数据解读中应予以充分考虑。本研究结果对基于eDNA进行的鱼类多样性调查提供了引物选择的依据, 同时为淡水生态系统的生物多样性保护提供了技术支持。